Static properties and stability of super-long span aluminum alloy mega-latticed structures. (October 2021) - Tan, Yilinke; Zhang, Yu; Zhang, Qingwen; Fan, Feng
Graphical abstract: Highlights: The joint stiffness was first discussed and a proper simulation method was proposed. A comparison of aluminum alloy and steel mega-latticed structures was undertaken. The force distribution of mega-latticed structures was illustrated and discussed. Suitable forms and spans of aluminum alloy mega-latticed structures were obtained. Parametric analysis of aluminum alloy mega-latticed structures was conducted. Abstract: Two types of aluminum alloy mega-latticed structures were generated through ANSYS to investigate the suitable material and form for super-long span spatial structures. The joint stiffness of the structures was first discussed, and a proper simulation method for the joints was proposed. Subsequently, the analysis of these two structures with spans from 800 m to 1200 m was conducted by emphasizing the peculiar differences with steel ones, based on the mechanical performance and economic indices. Also, the reasons for these differences were analyzed in detail. It was found that both structures had good mechanical performance, but the aluminum alloy structures had much better economic indices for spans greater than 1000 m. The material consumptions of the aluminum alloy structures were 1/3–1/7 of those of the steel structures at spans from 800 m to 1200 m. The aluminum alloy structures are more sensitive to wind but less sensitive to node imperfections than the steel structures. To further explore the applicability of aluminum alloy structures, the static and stability performance of structures with spans of 1600 m and 2000 m were analyzed. This showed that these super-long span structures could have excellent mechanical performance. Finally, four key structural parameters, namely support conditions, sections of the 3D trussed beams, sections of the chord members, and rise-span ratios, were examined. The influences of these parameters were thereby identified, and some reasonable values of these parameters were obtained. This work may provide a reference for the design and application of aluminum alloy mega-latticed structures.